Integrating content and language in English language teaching in secondary education: Models, benefits, and challenges - Banegas, Darío Luis (Studies in Second Language Learning and Teaching, 2012)
In the last decade, there has been a major interest in content-based instruction (CBI) and content and language integrated learning (CLIL). These are similar approaches which integrate content and foreign/second language learning through various methodologies and models as a result of different implementations around the world. In this paper, I first offer a sociocultural view of CBI-CLIL. Secondly, I define language and content as vital components in CBI-CLIL. Thirdly, I review the origins of CBI and the continuum perspective, and CLIL definitions and models featured in the literature. Fourth, I summarise current aspects around research in programme evaluation. Last, I review the benefits and challenges of this innovative approach so as to encourage critically context-responsive endeavours.